Characterization of memory T cells in individuals resistant to Schistosoma mansoni infection. (8th October 2019) - de Souza, Robson da Paixão; Araújo, Maria Ilma; Lopes, Diego Mota; de Almeida, Tarcísio Vila Verde Santana; Page, Brady; Oliveira, Ricardo Riccio; Carvalho, Edgar M.; Cardoso, Luciana Santos
Abstract: Schistosomiasis affects about 240 million people worldwide and is estimated that about 700 million people live in areas at risk of infection. In the context of immune response associated with infection by Schistosoma mansoni, the role of memory T cells is not well understood. Aim: To evaluate the frequency of memory CD4 + and CD8 + T cells from individuals resistant and susceptible to Schistosoma mansoni infection. Methods and Results: We selected individuals with low (resistant) and high (susceptible) parasite burden using databases generated during previous studies carried out in the same endemic area. The cell surface markers were performed using flow cytometry. In this study, the resistant individuals showed an increase in the CD4 + memory T‐cell pool associated with an increase in the central memory cell (TCM) and a decrease in the effector memory cell (TEM ). Individuals susceptible to infection had higher frequencies of effector memory cells compared to resistant individuals. Conclusions: These data suggest that resistance to S mansoni infection may be associated with an increase in the number of CD4 + memory T cells and susceptibility to infection is associated with a decrease in the central memory cell as well as high proportions of effector memory cells.